2021
DOI: 10.3390/ijms22063049
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis and Dialysis Therapies Differently Affect Nitric Oxide Synthetic Pathway in Red Blood Cells from Uremic Patients: Focus on Peritoneal Dialysis

Abstract: Red blood cells (RBCs) have been found to synthesize and release both nitric oxide (NO) and cyclic guanosine monophosphate (cGMP), contributing to systemic NO bioavailability. These RBC functions resulted impaired in chronic kidney disease (CKD). This study aimed to evaluate whether predialysis (conservative therapy, CT) and dialysis (peritoneal dialysis, PD; hemodialysis, HD) therapies used during CKD progression may differently affect NO-synthetic pathway in RBCs. Our data demonstrated that compared to PD, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Among these, a compensatory increase of RBC-NO synthase activation is included. In their article Palmerini et al [9] reported the impact of renal disease stage and therapeutic strategy (conservative therapy in stage 3 or 4 patients, peritoneal dialysis or hemodialysis in stage 5 patients) on the synthetic NO pathway activity in RBC from uremic patients. They found that the typical three therapeutic approaches affect at a variable way the ATPase activity of the cyclic guanosine monophosphate (cGMP, a biological effector of NO) transporter located on the RBC membrane, leading to lower efflux, and thus to higher cGMP accumulation inside RBC in conservative therapy and hemodialysis compared to the peritoneal dialysis.…”
mentioning
confidence: 99%
“…Among these, a compensatory increase of RBC-NO synthase activation is included. In their article Palmerini et al [9] reported the impact of renal disease stage and therapeutic strategy (conservative therapy in stage 3 or 4 patients, peritoneal dialysis or hemodialysis in stage 5 patients) on the synthetic NO pathway activity in RBC from uremic patients. They found that the typical three therapeutic approaches affect at a variable way the ATPase activity of the cyclic guanosine monophosphate (cGMP, a biological effector of NO) transporter located on the RBC membrane, leading to lower efflux, and thus to higher cGMP accumulation inside RBC in conservative therapy and hemodialysis compared to the peritoneal dialysis.…”
mentioning
confidence: 99%